2012
DOI: 10.1097/01.pra.0000413274.09305.9c
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Cannabinoid Use

Abstract: In the past few years, synthetic cannabinoid products have been increasingly used by adolescents and young adults. These products are marketed as herbal or aromatic incense and potpourri, but their psychoactive properties appear to be due to the addition of synthetic cannabinoids. When smoked, they can produce significant psychoactive and physical effects similar to cannabis. Changes in cognition, behavioral disturbances, alterations in mood, and perceptual changes have been reported. An emerging body of liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…To our knowledge, there is a limited number of available laboratory human studies investigating the association between persistence consumption of SC with WM performance. Yet, Castellanos and Thornton (2011) reported that young adults who used SC drugs experienced alterations in short-term memory; however, their main symptom was a severe psychotic episode [ 127 ]. Further reports described similar clinical manifestations where SC users experienced symptoms including alterations in short-term memory [ 128 , 129 ].…”
Section: Executive Function (Ef) and The Long-term Effects Of Cannmentioning
confidence: 99%
“…To our knowledge, there is a limited number of available laboratory human studies investigating the association between persistence consumption of SC with WM performance. Yet, Castellanos and Thornton (2011) reported that young adults who used SC drugs experienced alterations in short-term memory; however, their main symptom was a severe psychotic episode [ 127 ]. Further reports described similar clinical manifestations where SC users experienced symptoms including alterations in short-term memory [ 128 , 129 ].…”
Section: Executive Function (Ef) and The Long-term Effects Of Cannmentioning
confidence: 99%
“…As one synthetic cannabinoid is banned, others are produced to take their place as there are over 140 different Spice drugs that are produced (74). They may be marked as some type of “incense” or “herbal” product and even “air fresheners” but potential adverse reactions remain (77, 78). Toxicology screens looking at THC may miss the presence of these cannabinoid designer drugs (77, 79).…”
Section: Prevalencementioning
confidence: 99%
“…There have been several excellent reviews on the Spice phenomenon that have covered many of the important issues (Ashton 2012; Bhatty and Wu 2013; Castellanos and Thornton 2012; Fattore and Fratta 2011; Gunderson et al 2012; Harris and Brown 2013; Loeffler et al 2012; McGuinness and Newell 2012; Psychoyos and Vinod 2013; Seely et al 2012). Building on existing reviews, our paper examines aspects not previously covered by including the rich, informative literature on the subjective effects of Spice posted on the Erowid website.…”
Section: Introductionmentioning
confidence: 99%